2016
DOI: 10.1038/srep29270
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Nine Polymorphisms in EXO1 and Cancer Susceptibility: A Systematic Review and Meta-Analysis of 39 Case-control Studies

Abstract: An increasing number of studies have highlighted the potential link between EXO1 polymorphisms and cancer risk, although no consensus has yet been obtained. Thus, we aimed to obtain a thorough and current assessment of EXO1 polymorphisms and cancer susceptibility by performing a meta-analysis. A comprehensive literature retrieval was performed on PubMed, EMbase, Web of Science and Wanfang databases. The odds ratio (OR) and 95% confidence interval (CI) were applied to assess the results. Finally, 39 case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…It is well in accordance with the theory of the driver and passenger somatic mutations in human cancer genome 26. Rs851797, located at 3′-UTR of EXO1 gene, was found to be associated with risk of several human cancers 11. In silico analysis by using the RNAfold online tool showed that rs851797 could alter the local secondary structure of the EXO1 mRNA based on the MFE value, thus contribute to tumor progression and prognosis.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It is well in accordance with the theory of the driver and passenger somatic mutations in human cancer genome 26. Rs851797, located at 3′-UTR of EXO1 gene, was found to be associated with risk of several human cancers 11. In silico analysis by using the RNAfold online tool showed that rs851797 could alter the local secondary structure of the EXO1 mRNA based on the MFE value, thus contribute to tumor progression and prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…Meta-analysis showed that EXO1 rs851797 was conferred an increased overall susceptibility to cancer in an allelic model 11. Recently, a pooled genome-wide association study reported that the EXO1 polymorphism region (1q43) was associated with the risk of EOC 17.…”
Section: Discussionmentioning
confidence: 99%
“…EXO1, a DNA mismatch repair gene, its polymorphisms have been reported to play a critical role in the development of many tumors (Shi et al, 2017;Zhang et al, 2016). Also, due to its role in DNA replication repair and homology-directed repair, the relationships of EXO1 and BRCA1/2 mutations and its underlying mechanism have become an important focus to be studied (Lemacon et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Only a variant in gene EXO1 (NM_130398.3:c.*84T>G) was predicted as a likely true candidate for affecting miRNA binding, for miR-370-3p and miR-93-3p (see S3 Table ). Several studies have shown the importance of EXO1 in replication, DNA repair pathways, cell cycle checkpoints and its association to cancer [ 76 ], and GWAS studies have identified specific mutations in EXO1 gene as risk alleles for different types of cancer [ 77 , 78 ]. SNPs in miRNA binding sites have been associated with CRC [ 79 ].…”
Section: Resultsmentioning
confidence: 99%